Bibliographical research on the implementation of automation in fish farming - Amorim, Matheus de Jesus; Sousa, Gabriéla Ramalho; Tosta, Marielce de Cássia Ribeiro (Brazilian Journal of Production Engineering, 2021)
The use of automation technologies, can improve aquaculture production, in order to favor productivity and product quality. The future of this trade depends mainly on how the industry will conduct the process of automating its production. That said, the objective of this study was to analyze the increase in productivity resulting from the use of automation in feeding and monitoring of water quality, in addition to describing the projects carried out for this purpose and the companies that provide such services. For this, a bibliographic review was carried out to gather information about the prototypes and, in addition, contact was made with some companies that provide the automation service in whole or in part. As a result, it was possible to notice that there are several possibilities for implementing automation in fish farming, varying the implementation costs from low to high and according to the fish farmer's needs.
Keywords: Fish farmer; Productivity; Quality; Automation.